2018
DOI: 10.1007/s00266-018-1271-2
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Improved the First Stages of Wound Healing Process After Abdominoplasty: An Experimental, Double-Blinded, Non-randomized Clinical Trial

Abstract: Background Photobiomodulation is widely studied for its potential benefits in the wound healing process. Numerous scientific studies have highlighted its effect on various phases of wound repair, but clinical validations are few. This comparative trial aims to evaluate the influence of photobiomodulation on the post-abdominoplasty healing process. Methods Seventeen Caucasian women (aged 18-55) who underwent an abdominoplasty were enrolled in this doubleblinded, controlled clinical trial. The postoperative scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
2
11
0
2
Order By: Relevance
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence biomodulation (FB), a form of PBM that uniquely employs fluorescence light energy (FLE), has been demonstrated to advance healing of both acute and chronic wounds [22,[29][30][31]33]. A study has demonstrated that acute incisional wounds have reduced inflammation, as well as more physiologic re-epithelization and collagen remodelling, resulting in better quality and less visible scars [21]. In a multicenter, observational, uncontrolled trial, patients with hard-to-heal chronic ulcers experienced accelerated healing and improved quality of life [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was a lack of randomization, the authors were able to minimize other biases affecting the internal validity of the study by blinding the patients and outcome assessors to the patient's treatment allocation. 23 On the other hand, external validity refers to the generalizability of the results to the population, which evaluates the ability to apply a study's conclusions outside of the context of that study. 13 Therefore, to present evidence that is generalizable, authors of EBM articles should aim to include results from studies with clear eligibility criteria and large sample size.…”
Section: Pitfallsmentioning
confidence: 99%
“…So the prevention of hypertrophic scars and keloids is still a considerable problem for cosmetic surgeries [4]. Mammoplasty and abdominoplasty are widely performed plastic surgeries worldwide with high level of patients' satisfaction, but associated with serious and sometimes cosmetic complications like hypertrophic scars and keloids, principal causes of patient and surgeon dissatisfaction [5].…”
Section: Introductionmentioning
confidence: 99%